Peningkatan Belajar siswa Melalui Metode Teams Group Turnamnet (TgT) Dalam Mata Pelajaran Pendidikan Agama Islam Kelas VII SMP Islam Uluwwul Himmah Marendal 1 - Indah Doa Nita; Nurman Ginting (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
Interesting learning for students is something that must be done so that learning is more meaningful. In presenting learning in the classroom, the teacher does not only convey material using methods or strategies, but the teacher is also required to master several learning models. In fact, the model that is often used by teachers in the learning process in PAI subjects is the Lecture model. This learning model should be changed by the teacher so that the learning process is more creative, active and meaningful. Improving learning outcomes and effectiveness in the PAI learning process has been carried out through various efforts, one of which is the use of the TGT cooperative learning model. Cooperative learning model is designed to educate group cooperation and interaction between students. So there is a need for an overall re-analysis in a study to see how much cooperative learning increases on learning outcomes and how the learning process is carried out. In this study, researchers used qualitative research methods. The average increase in student learning outcomes using the TGT cooperative learning model in science subjects in schools, both elementary and junior high school children, is very influential.